2006
DOI: 10.1007/s11145-006-9018-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental influences on prereading skills and early reading and spelling development in the United States, Australia, and Scandinavia

Abstract: Genetic and environmental relations between vocabulary and reading skills were explored longitudinally from preschool through grades 2 and 4. At preschool there were strong sharedenvironment and weak genetic influences on both vocabulary and print knowledge, but substantial differences in their source. Separation of etiology for vocabulary and reading continued for word recognition and decoding through grade 4, but genetic and environmental correlations between vocabulary and reading comprehension approached u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 37 publications
5
73
2
Order By: Relevance
“…Therefore, should it be the case that heritability increases with age, our estimate would represent an average over the lifespan and will therefore be somewhat higher than if it were based on younger twins alone. In addition, we found a somewhat larger component of E on reading ability compared to other genetic studies which found estimates around 10% (Harlaar, Spinath, Dale, & Plomin, 2005;Samuelsson et al, 2007). This may reflect larger measurement error, or reflect genuine environmental influences that are not shared among family members.…”
Section: Discussioncontrasting
confidence: 56%
“…Therefore, should it be the case that heritability increases with age, our estimate would represent an average over the lifespan and will therefore be somewhat higher than if it were based on younger twins alone. In addition, we found a somewhat larger component of E on reading ability compared to other genetic studies which found estimates around 10% (Harlaar, Spinath, Dale, & Plomin, 2005;Samuelsson et al, 2007). This may reflect larger measurement error, or reflect genuine environmental influences that are not shared among family members.…”
Section: Discussioncontrasting
confidence: 56%
“…The study by Samuelsson et al (2007) was the first to compare genetic and environmental contributions to literacy skills as a function of intensity of reading instruction in kindergarten. By comparing an Australian twin sample entering a school system with strong emphasis on literacy instruction with U.S. twins receiving approximately half the time of instruction, estimated heritability was 1.5 and 2.5 times higher in Australia on reading and spelling, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In this article, we continue to report on our International Longitudinal Twin Study (ILTS) of early language and literacy development (Byrne et al 2002;Byrne et al 2005;Byrne et al 2006;Byrne et al 2007;Samuelsson et al 2007;Willcutt et al 2007). The main purpose here was to compare genetic and environmental influences on early reading and spelling skills across three twin samples tested in the United States, Australia, and Scandinavia (i.e., Sweden and Norway) and across time of testing (i.e., kindergarten and Grade 1).…”
mentioning
confidence: 99%
“…In longitudinal studies, naming speed has proven to be rather stable and naming speed deficits appear to be persistent in nature (e.g., Powell, Stainthorp, & Stuart, 2014). Some part of this stability can be explained by genetic sources, as a strong genetic influence has been shown in RAN performance (e.g., Byrne et al, 2006;Christopher et al, 2015;Davis et al, 2001;Petrill, Deater-Deckard, Thompson, DeThorne, & Schatschneider, 2006;Petrill et al, 2010;Samuelsson et al, 2007). There is also recent research evidence for specific genes that have been associated with RAN performance (Naples, Chang, Katz, & Grigorenko, 2009), some of them the same as those previously associated with dyslexia (Rubenstein, Raskind, Berninger, Matsushita, & Wijsman, 2014).…”
Section: What Is Rapid Automatized Naming (Ran)?mentioning
confidence: 99%